Muscle spindle afferent neurons preferentially degenerate with aging - Minako Kawai-Takaishi; Tohru Hosoyama (Scientific Reports)
Abstract Muscle spindles sense changes in muscle length and transmit them to the central nervous system. Proprioception is essential for gait and postural maintenance, the abnormality of which has been linked to gait disorders and the risk of falling in older adults. However, the effects of aging on the muscle spindle structure remain nebulous. This study investigated age-related structural changes in the muscle spindles (from the equator to the polar) in the soleus and extensor digitorum longus (EDL) muscles of young, middle-aged, and aged mice. The findings indicated that the shape of the annulospiral endings of the sensory neurons began to deteriorate in middle-aged compared with young mice and was further exacerbated in aged mice. These changes were particularly pronounced in the nuclear bag fibers, whereas no significant age-related changes were observed in the intrafusal fibers or capsules. A decline in gait function due to changes in weight-bearing and weight-shifting in aged mice was also observed, suggesting that the deterioration of proprioceptive sensory neurons that innervate the nuclear bag fiber responsible for dynamic sensitivity prevents proper coordinated movement and contributes to movement disorders in aged animals including humans, together with the functional decline of extrafusal fibers.